Quantitative proteomic analysis of the Anopheles gambiae (Diptera: Culicidae) midgut infected with o’nyong–nyong virus - Rider, Mark A.; Zou, Jin; Vanlandingham, Dana L.; Nuckols, John T.; Higgs, Stephen; Zhang, Qiang; Lacey, Michelle; Kim, Joohyun; Wang, Guangdi; Hong, Young S. (My University, 2013)
Alphaviruses are arthropod-borne pathogens that infect a range of hosts. In humans and other mammals, alphavirus infection can cause severe disease. In mosquito hosts, however, there are generally few symptoms. Little is known about the cellular responses of mosquitoes that allow them to cope with infection. In this investigation, a six-plex tandem mass tagging proteomic approach was used to study protein accumulation changes in the midgut of Anopheles gambiae (Giles) (Diptera: Culicidae) mosquitoes infected with o'nyong-nyong virus (Togaviridae, Alphavirus). Five hundred thirty-six nonredundant proteins were identified. Twenty-two were found in significantly different quantities in infected midguts compared with controls. Of interest, analysis revealed molecular pathways possibly targeted by virus proteins, such as those involving TAF4 and DNA polymerase phi proteins. Also identified was an FK506-binding protein. FK506-binding protein orthologs have been described as conserved host resistance factors, which suppress dengue and West Nile virus infection in human HeLa cells. This investigation constitutes the first study of the midgut-specific proteome of An. gambiae in relation to alphavirus infection. Our findings offer insight into mosquito immunity, including factors that possibly contribute to the different pathological outcomes observed in vertebrate and insect hosts.
Keywords: O'nyong-nyong virus; Anopheles gambiae; Tandem mass tag; FK506-binding protein; Midgut